Chronic ingestion of sodium and potassium bicarbonate, with potassium, magnesium and calcium citrate improves anaerobic performance in elite soccer players - Chycki, J.; Golas, A.; Halz, M.; Maszczyk, A.; Toborek, M.; Zajac, A. (Nutrients, 2018)
Anaerobic power and anaerobic capacity significantly influence performance in many sport disciplines. These include prolonged sprints in athletics, swimming, or cycling, and other high intensity intermittent sports, such as soccer or basketball. Considering the association of exercise-induced acidosis and fatigue, the ingestion of potential buffering agents such as sodium bicarbonate, has been suggested to attenuate metabolic acidosis and improve anaerobic performance. Since elite soccer players cover from 200 to 350 m while sprinting, performing 40-60 all out sprints during a game, it seems that repeated sprint ability in soccer players is among the key components of success. In our experiment, we evaluated the effectiveness of chronic supplementation with sodium and potassium bicarbonate, fortified with minerals, on speed and speed endurance in elite soccer players. Twenty-six soccer players participated in the study. The subjects were randomly divided into two groups. The experimental group was supplemented with sodium bi-carbonate and potassium di-carbonate fortified with minerals, while the control group received a placebo. The athletes were tested at baseline and after nine days of supplementation. Anaerobic performance was evaluated by the Repeated Anaerobic Sprint Test (RAST) protocol which involved 6 × 30 m max sprints, separated by 10 s of active recovery. Resting, post ingestion and post exercise concentrations of HCO3- and blood pH were measured as well as lactate concentration. The current investigation demonstrated a significant increase in RAST performance of elite soccer players supplemented with sodium and potassium bicarbonate along with calcium phosphate, potassium citrate, and magnesium citrate ingested twice a day over a nine-day training period. The improvements in anaerobic performance were caused by increased resting blood pH and bicarbonate levels.